Typological Analysis of Façade Elements in Madrasah Terpadu Kota Malang Building Complex - Ahmad Daffa Barentra (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
Facade in the architectural design of a building serves as its identity. Madrasah Terpadu Kota Malang serves as a model in Indonesia, yet it lacks architectural design guidelines for building facades that could be used as a reference. The complex shares a common education concept, all situated within one site.Typological studies combine the specific characteristics of a group of architectural works that differ in detail from one another (Karen, 2005). A qualitative descriptive method was used, employing observations to identify facade elements within Madrasah Terpadu Kota Malang. The research categories encompass functional, harmony, and narrative elements within the facade.Within the functional category, there is an Islamic architectural character expressed through the use of natural colors. Window openings are grouped within a single plane. Within the harmony category, proportions are evident through the central part which appears prominent compared to its surroundings, while maintaining consistency in the use of materials. The facade exhibits a closed envelope with decorative elements following the Eyvan concept. Narrative elements display a dynamic rhythm in window elements. Vertical articulation employs The Hypostyle Mosque concept, while horizontal articulation utilizes element accents. The secondary skin served as a foreground effect, with the surroundings as the background.